1999
DOI: 10.1037/1089-2680.3.4.317
|View full text |Cite
|
Sign up to set email alerts
|

Control and Efficacy as Interdisciplinary Bridges

Abstract: Control and efficacy are ideally suited as “bridges” or linking constructs for social scientists working at different levels of analysis. Control and efficacy depend on the fit between individuals and the social systems in which they are embedded, and control and efficacy have measurable effects on neurotransmitter levels and endocrine responses. This article presents an interdisciplinary perspective on control and efficacy. The authors survey the history of control-related constructs in psychology, from their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
103
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(106 citation statements)
references
References 107 publications
1
103
0
2
Order By: Relevance
“…Previous research on the relationship between perceived control and stress has shown that perceptions of control impact both individuals' psychological and physiological reactions to stressors (e.g. van Eck, Nicolson, & Berkhof, 1998;Haidt & Rodin, 1999). Having a sense of control over one's stressors has been shown to be related to successful coping after stressful events (Lazarus, 1981;Lazarus & Folkman, 1984), increased resistance to health threats (Marks, Murray, Evans, & Willig, 2000) and emotional well-being (Thompson & Spacapan, 1991).…”
Section: Variables Infl Uencing the Hassle-stress Relationshipmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research on the relationship between perceived control and stress has shown that perceptions of control impact both individuals' psychological and physiological reactions to stressors (e.g. van Eck, Nicolson, & Berkhof, 1998;Haidt & Rodin, 1999). Having a sense of control over one's stressors has been shown to be related to successful coping after stressful events (Lazarus, 1981;Lazarus & Folkman, 1984), increased resistance to health threats (Marks, Murray, Evans, & Willig, 2000) and emotional well-being (Thompson & Spacapan, 1991).…”
Section: Variables Infl Uencing the Hassle-stress Relationshipmentioning
confidence: 99%
“…The construct of control has frequently been identifi ed in the literature as an important variable in the stress process (Folkman, 1984;Haidt & Rodin, 1999;Rotter, 1990;Taylor & Aspinwall, 1996;Troup & Dewe, 2002), and refers to an individual's sense of infl uence over events and their reactions to events (Stoyva & Carlson, 1993;Taylor & Aspinwall, 1996). Previous research on the relationship between perceived control and stress has shown that perceptions of control impact both individuals' psychological and physiological reactions to stressors (e.g.…”
Section: Variables Infl Uencing the Hassle-stress Relationshipmentioning
confidence: 99%
“…The self-efficacy construct is differently interpreted in the various papers and a large number of evaluation scales have been used, some of which very poor in terms of psychometric goodness [4][5][6][7]. In rehabilitation setting, patients affected by chronic diseases may have the capability to adjust continuously their coping through a flexible range of responses to life changes.…”
Section: Introductionmentioning
confidence: 99%
“…Allowing rodents to escape or control when a negative stressor, such as an electric shock, ends increases tumor rejection, reduces tumor growth and increases lymphocyte stimulation 51,52 . Furthermore, even the perception of control is sufficient to elicit the same psychophysiological buffering to a stressor as actual control 53 . Glass and Singer 54 illustrated this by exposing human participants to loud noise.…”
Section: Thermal Stress and Its Effect On Mouse Modelsmentioning
confidence: 99%